Contact lens-associated superficial stromal keratitis caused by Paecilomyces lilacinus - Huebner, L.; Tourtas, T.; Weller, J. (Ophthalmologe, 2020)
This article presents two cases of contact lens wearers with keratitis caused by Paecilomyces lilacinus. The special feature of these cases was the superficial manifestation of the infection in the upper stromal layer without infiltration into deeper layers. The pathogen was identified following epithelial debridement and corneal scraping. In both cases the fungal keratitis could be successfully managed by intensive topical treatment with voriconazole. Except for an epithelial debridement with EDTA chelation and an amniotic membrane transplantation in one case, no further surgical interventions were necessary.
CRIS-Team WoS Importer:2020-04-10